Pengaruh Kompetensi Kepribadian dan Kompetensi Sosial Terhadap Kinerja Guru di Sekolah Menengah Atas (SMA) Negeri 9 Pekanbaru - Darmawansyah Putra (ALBAHRU, 2022)
This research is motivated by the problem that personal competence and social competence at State Senior High School (SMA) 9 Pekanbaru is good. Nevertheless, the teachers’ work performance is still low. Therefore, this research is aimed at exploring that problem. In collecting the data, questionnaire, observation, and documentation are used. The data analysis technique uses multiple linier regression method by using SPSS 17.0. The results of this research are: First, there is a significant and positive effect between personal competence (X1) and teacher work performance (Y), this is the result of T-test by T-Count value of variable X1 = 4.414 > 2.000 that Ha is accepted and Ho is rejected which means the independent variable (X1), personal competence partially has a significant effect toward the dependent variable (Y), the teachers’ work performance at State Senior High School (SMA) 9 Pekanbaru. Secondly, there is an effect between social competence and the teachers’ work performance, indicated from T-test by T-Count of X2 variable = 2.897 > 2.000 that Ha is accepted and Ho is rejected which means that the independent variable (X2) the social competence partially has a significant effect toward dependent variable (Y), the teachers’ work performance at State Senior High School (SMA) 9 Pekanbaru. Third, there is an effect simultaneously between the personal competence and social competence toward the teachers’ work performance. It is gained from the result of F test from which the score of F-count is 41.583 with the significant rate of 0.000. While F-table in the reliance rate of 95% (0.05) is 3.13. in both count, F-count > F-Table and the significance rate is 41.593 > 3.13. It means that simultaneously, personal competence and social competence has a significant toward the teachers’ work performance.